The voltage dip and doubly fed induction generator with considering uncertainty conditions - Zahra Rafiee; Mansour Rafiee; Mohammad Reza Aghamohammadi (Institute of Advanced Engineering and Science, 2020)
The paper presents the transient behavior of the doubly fed induction generator (DFIG) in the wind turbine (WT) in the normal and voltage dip condition. When voltage dip occurs in to the grid, the rotor current increases and the DC-link voltage increases too and start to oscilate. In this paper, the proportional integral (PI) controllers are used to control the DFIG-basedwind farms for regulating the electronic devices including rotor side converter (RSC) and grid side converter (GSC) to control the active and reactive power of DFIG. The PI parameters are tuned by imperialist competitive algorithm (ICA). So, the transient behavour of the DFIG-based WF is explors when the voltage dip occurs. Hence, the induced electric motive force in to the rotor is measured. Also, an existed uncertainty for mutual inductance is considered caused by saturated curve during three-phase fault conditions and the bahavour of DFIG-based WT is examined and analyzed. All of simulation is done by Matlab/Simulink®.